3D Printing of Diamond Tools for Dental Ceramics Processing. Issue 3 (15th November 2017) - Yang, Zhibo; Hu, Junchen; Li, Kaiqiang; Liu, Aiju; Liu, Shian
Abstract : This paper is focused on preparing diamond tools with orderly arranged abrasive particles for dental ceramics processing via 3D printing. This allows one to overcome such drawbacks of the existing methods of dental ceramics processing as weak bonding strength, short service life, and irregular diamond distribution in diamond tools. Firstly, the CAD model of the dental diamond tool is constructed using 3D cartographic software, with level‐scan‐path geometry information generated via hierarchcal slicing. Then, using Ni–Cr alloy powder and diamond as raw materials, the dental ceramics processing diamond tool with orderly arranged diamond particles is prepared via a 3D printer. Next, an X‐ray diffractometer, energy dispersive spectrometer, and scanning electron microscope are used to analyze the microstructure of the Ni–Cr alloy and diamond particle interfaces, resulting in the identification of their bonding mechanism. Finally, the diamond grinding wheel produced by 3D printing is subjected to dental zirconia ceramics grinding performance tests. The results obtained confirm that diamond particles experience normal wear, while no abrasive falling off occurs on the 3D printed diamond tool surface. Abstract : In this paper, diamond tools for dental ceramics processing are manufactured using the 3D printing technology. Laser fast scanning is utilized to make the 3D distribution of diamond particles more regular, thus, significantly improving the manufacturing performance of grinding wheels.